Role of Improved Seeds Technology to Increase Production and Crop Diversification in Nepal - Wagle, ShyamPrasad (Rupantaran: A Multidisciplinary Journal, 2022)
This paper deals with the possibilities and challenges through the impact of using improved seeds technologies on crop production particularly in the case of the eastern hilly area of Nepal. The study applied househod questionnaire survey, key informant survey and field observation to collect relevant information. The study conducted in 30 percent (180hss) in total (601hhs) of three altitude belts such as upper, middle and lower, ranging from 300 to 2,250 masl along the Koshi-highway. Secondary data were gathered from previous research journals, dissertations and official records. This paper has revealed that improved seeds technology is known as well known and profitable technology for the promotion of both fruits and crops farming in the study area. More than 84 percent (152hhs) farmers have used this as a useful and profitable innovation. Despite various problems, the attraction of farmers is gradually increasing towards this technology. The maximum effort of the farmers seems to be use newly developed hybrid seeds in their agricultural works as far as possible. Although it was introduced through the inspiration of local research centers at first time, the role of neighbours, friends/ relatives and television programs seems to be significant respectively in its development and expansion of this technology in the study area. Less tasty, lack of proper knowledge to use this technology, high investment and lack of immunity are major identified problems associated with this technology.